2020
DOI: 10.1016/j.jse.2019.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic rotator cuff repair using a transosseous knotless anchor (ATOK)

Abstract: Background: This article reviews the clinical and radiographic outcomes in a noninferiority trial use of a transosseous knotless anchor to perform arthroscopic rotator cuff repairs in a patient cohort that have an increased incidence of osteoporosis. Methods: Patients aged over 60 with a documented rotator cuff tear and who failed a rehab program underwent repair using an arthroscopic transosseous knotless (ATOK) anchor. Patients were prospectively reviewed using shoulder functional assessments (age-adjusted C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Among the orthopedic complaints, shoulder pain ranks third following knee pain and low back pain [1]. Arthroscopy procedure for the treatment of shoulder joint diseases is a frequently used treatment method [2].…”
Section: Introductionmentioning
confidence: 99%
“…Among the orthopedic complaints, shoulder pain ranks third following knee pain and low back pain [1]. Arthroscopy procedure for the treatment of shoulder joint diseases is a frequently used treatment method [2].…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were also reported previously in comparable outcome studies where suture anchors had been used. 3 , 10 More recently, Sandow and Schutz 27 described satisfactory functional and anatomical results with a TO repair in an osteoporotic cohort of 15. Similarly, Arican et al 2 described satisfactory clinical outcomes at >2 years in 70 patients treated with TO repair.…”
Section: Discussionmentioning
confidence: 98%
“… 47 A previous study 25 suggested that double-row sutures result in more favorable structural healing compared with SR sutures. Sandow and Schutz 40 demonstrated that arthroscopic rotator cuff repair using transosseous knotless anchors provides satisfactory healing and anchor stability, enabling the achievement of high functional recovery. Kim et al 22 reported that superior bone ingrowth could be achieved with open-construct PEEK anchors than with nonvented biocomposite anchors at early healing stages.…”
Section: Discussionmentioning
confidence: 99%